2018
DOI: 10.1039/c8cy01147h
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the interlayer cations of birnessite-type MnO2 to enhance its oxidation ability for gaseous benzene with water resistance

Abstract: The Cu–MnO2 catalyst exhibited good resistance to high-temperature deactivation and water poisoning as well as good stability during long-term testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 71 publications
4
15
0
Order By: Relevance
“…The substitution of Mn by the dopants facilitated the generation of oxygen vacancies and the mobility of lattice oxygen, leading to the generation of more active surface oxygen species. Similar observations were reported for Cu-doped δ-MnO 2 for toluene and benzene oxidation, with significantly lower temperature activities compared to the unmodified δ-MnO 2 , owing to the formation of oxygen vacancies and its resultant effect on low-temperature reducibility and lattice oxygen reactivity. Doping Cu into the octahedra framework of δ-MnO 2 was also shown to reduce the electron-transfer resistance of δ-MnO 2 , thereby enhancing its catalytic activity and stability for oxygen reduction reaction .…”
Section: Introductionsupporting
confidence: 84%
“…The substitution of Mn by the dopants facilitated the generation of oxygen vacancies and the mobility of lattice oxygen, leading to the generation of more active surface oxygen species. Similar observations were reported for Cu-doped δ-MnO 2 for toluene and benzene oxidation, with significantly lower temperature activities compared to the unmodified δ-MnO 2 , owing to the formation of oxygen vacancies and its resultant effect on low-temperature reducibility and lattice oxygen reactivity. Doping Cu into the octahedra framework of δ-MnO 2 was also shown to reduce the electron-transfer resistance of δ-MnO 2 , thereby enhancing its catalytic activity and stability for oxygen reduction reaction .…”
Section: Introductionsupporting
confidence: 84%
“…Besides, the strategies such as metal doping and loading have been investigated to improve the catalytic activities on benzene combustion over MnO 2 . Liu et al 147 found that the Ce 3+ and Cu 2+ doped of MnO 2 nanosheet could significantly improve the activity of MnO 2 for benzene decomposition. For the pristine MnO 2 , benzene was hardly decomposed below 200 °C and only ∼40% conversion was achieved at 400 °C.…”
Section: Application In Catalytic Oxidationmentioning
confidence: 99%
“…Although significant progress has been made in benzene oxidation over acid-modified LiCoO 2 catalysts, the activity of the H-LiCo-6 catalyst still needed improving, especially when compared with our previously reported Cu 2+ -exchanged birnessite MnO 2 , which exhibited superior activity over the samples of similar type. Considering how challenging it is to break the refractory chemical bonds of benzene molecule, the H-LiCo-6 sample in this study was still promising for benzene oxidation in the gas phase.…”
Section: Results and Discussionmentioning
confidence: 72%
“…Benzene is one of the commonly found volatile organic compounds (VOCs) in polluted air, recognized as hazardous contaminant. Due to its “teratogenesis, carcinogenesis, and mutagenesis”, benzene is posing a serious threat to human health. Moreover, the residual benzene is detected in animals, plants, soil and, bodies of water, and this potential harm will last for generations since benzene is refractory and difficult to decompose .…”
Section: Introductionmentioning
confidence: 99%